Portable diffuse reflectance infrared Fourier transform (DRIFT) technique for the non-invasive identification of canvas ground: IR spectra reference collection. Issue 6 (21st March 2015) - Manfredi, M.; Barberis, E.; Rava, A.; Robotti, E.; Gosetti, F.; Marengo, E.
<x xml:space="preserve">Abstract</x> Sixteen of the most important canvas grounds used since the XIV to the XX century were prepared following the ancient recipes (including grounds from Vasari, Caravaggio, and De Chirico) and a reference library of DRIFT spectra was built.